Sistema de mensuração de desempenho para centros de distribuição supermercadista - García, César Octavio Ramírez (2019)
Globalization causes changes in people's technology, society, culture and lifestyle, and supermarkets are constantly competing in this environment. Within the supply chain, there is an important component that if managed effectively and efficiently can bring competitive gains to supermarkets, otherwise it can lead to organizational failure. This important component is de warehouses management, which are responsible for creating a connection between suppliers and supermarkets. Warehouses management leaders manage and control all internal processes in order to keep all of them in sync with each other to ensure their productivity, efficiency and operations efficiency. For the complexity of managing the warehouses, leaders have difficulty managing and controlling the links or critical factors of their operations. Therefore, their management becomes a constant challenge that they have to endure. The objective of this research is to create a tool that will support leaders in decision making about the critical factors for which warehouses management are competing. This research is based on bibliographic studies of scientific journals and books, uses assumptions related to Key Performance Indicators (KPIs) and the concepts of multicriteria approach to decision support. The proposed modeling will be tested in warehouses of supermarket companies, where the results obtained will be analyzed and discussed. In order to strengthen the contribution of the study, recommendations will be made to each of the companies studied so that they are able to see their level of competitiveness with respect to modeling.